Humanized Drosophila Model of the Meier-Gorlin Syndrome Reveals Conserved and Divergent Features of the Orc6 Protein. Issue 4 (1st December 2020) - Balasov, Maxim; Akhmetova, Katarina; Chesnokov, Igor
Abstract: Orc6 is a component of the Origin Recognition Complex important for the initiation of DNA replication. In order to study the functions of Orc6 in vivo, Balasov, Akhmetova, and Chesnokov..... Abstract: Meier–Gorlin syndrome (MGS) is a rare, autosomal recessive disorder characterized by microtia, primordial dwarfism, small ears, and skeletal abnormalities. Patients with MGS often carry mutations in genes encoding the subunits of the Origin Recognition Complex (ORC), components of the prereplicative complex and replication machinery. Orc6 is an important component of ORC and has functions in both DNA replication and cytokinesis. A mutation in the conserved C-terminal motif of Orc6 associated with MGS impedes the interaction of Orc6 with core ORC. Recently, a new mutation in Orc6 was also identified; however, it is localized in the N-terminal domain of the protein. To study the functions of Orc6, we used the human gene to rescue the orc6 deletion in Drosophila . Using this "humanized" Orc6-based Drosophila model of MGS, we discovered that unlike the previous Y225S MGS mutation in Orc6, the K23E substitution in the N-terminal TFIIB-like domain of Orc6 disrupts the protein ability to bind DNA. Our studies revealed the importance of evolutionarily conserved and variable domains of Orc6 protein, and allowed the studies of human protein functions and the analysis of the critical amino acids in live animal heterologous system, as well as provided novel insights into the mechanisms underlying MGS pathology.